The Costs and Benefits of "Open Access" Scholarship - Altbach, Philip (International Higher Education, 2008)
The Harvard Faculty of Arts and Sciences recently joined the open access movement, urging its professors to post their research on an open access Harvard Web site. This movement may well ensure that scholars prominent in the world of knowledge remain a dominant force, while recognition of the work of others may prove to be more difficult. Traditional scholarly journal uses a means of selection, the peer-review system, which has served as the quality control, though this system also is imperfect. Open access, while it seems like an easy panacea, has problems that deserve careful consideration.